Astragaloside IV Alleviates Intestinal Barrier Dysfunction via the AKT-GSK3β-β-Catenin Pathway in Peritoneal Dialysis - He, Jiaqi; Wang, Mengling; Yang, Licai; Xin, Hong; Bian, Fan; Jiang, Gengru; Zhang, Xuemei (Frontiers in Pharmacology, 2022)
Background and aims: Long-term peritoneal dialysis (PD) causes intestinal dysfunction, including constipation, diarrhea, or enteric peritonitis. However, the etiology and pathogenesis of these complications are still unclear and there are no specific drugs available in the clinic. This study aims to determine whether Astragaloside IV (AS IV) has therapeutic value on PD-induced intestinal epithelial barrier dysfunction in vivo and in vitro. Methods: We established two different long-term PD treatment mice models by intraperitoneally injecting 4.25% dextrose-containing peritoneal dialysis fluid (PDF) in uremia mice and normal mice, which were served as controls. In addition, PDF was applied to T84 cells in vitro. The therapeutic effects of AS IV on PD-induced intestinal dysfunction were then examined by histopathological staining, transmission electron microscopy, western blotting, and reverse transcription polymerase chain reaction. The protein levels of protein kinase B (AKT), glycogen synthase kinase 3β (GSK-3β) and β-catenin were examined after administration of AS IV. Results: In the present study, AS IV maintained the intestinal crypt, microvilli and desmosome structures in an orderly arrangement and improved intestinal epithelial permeability with the up-regulation of tight junction proteins in vivo. Furthermore, AS IV protected T84 cells from PD-induced damage by improving cell viability, promoting wound healing, and increasing the expression of tight junction proteins. Additionally, AS IV treatment significantly increased the levels of phosphorylation of AKT, inhibited the activity GSK-3β, and ultimately resulted in the nuclear translocation and accumulation of β-catenin. Conclusion: These findings provide novel insight into the AS IV-mediated protection of the intestinal epithelial barrier from damage via the AKT-GSK3β-β-catenin signal axis during peritoneal dialysis.